Masker Gel Ekstrak Bunga Telang (Clitoria ternate L.) sebagai Antibakteri Staphylococcus aureus dan Staphylococcus epidermidis - Hasriana, Eli; Mayasari, Ulfayani (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
The aim of this research was to determine the effect of the antibacterial activity of butterfly pea flower extract and butterfly pea flower extract gel mask on Staphylococcus aureus bacteria and Staphylococcus epidermidis bacteria, as well as to determine the effective concentration of butterfly pea flower extract in inhibiting the growth of Staphylococcus aureus bacteria and Staphylococcus epidermidis bacteria. This research method is the disc method by measuring the inhibition zone of butterfly pea flower extract at several concentrations. The results of the research show that butterfly pea flower extract has activity in inhibiting the growth of Staphylococcus aureus and Staphylococcus epidermidis bacteria. The telang flower extract gel mask has antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis bacteria, and the concentrations that are effective in inhibiting bacterial growth are 17% and 19%. In conclusion, butterfly pea flower extract has been proven to have potential as an effective antibacterial agent against Staphylococcus aureus and Staphylococcus epidermidis, especially at certain concentrations. Keywords: Butterfly flower gel mask, Staphylococcus aureus, Staphylococcus epidermidi